OPTIMIZATION OF DIAGNOSTIC METHODS AND TREATMENT OF MOLECULAR AND BIOCHEMICAL MECHANISMS IN RECURRENT POLYCYSTIC OVARIES - Karimova, N.N.; Halimova , E.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This study studied the risk factors for the development of recurrent polycystic ovaries, the role of obesity in its development. For the study, 92 women with recurrent polycystic ovaries aged 19-35 years with and without obesity were studied in the control group of 20 healthy women living in the Bukhara region. The study concluded that hyperinsulinemia plays an important role in the development of the disease in patients with obesity-related OC, while dysfunction associated with the hypothalamic-pituitary system (induced by stress), on the other hand, plays an important role in the development of OCJ independently. from obesity in patients of the second group.